Comparative Study of Combustible Species for 4-stroke Otto Cycle Combustion Motor and 6-stroke MUB-2 Cycle Combustion Motor with Fuel Pertamax - Dedi Nurdiansyah; Sudjito Soeparman; Eko Siswanto (Universitas Muhammadiyah Sidoarjo, 2021)
This paper describes the ratio of levels of combustible species (CO, HC, CO2 and lambda) of a four-cycle otto motor with a six-stroke MUB-2 motor with additional combustion duration and two working steps. The increase in combustion duration aims to re-burn combustible species that have not been completely burned in the first combustion. This study used a 4 stroke motor with a capacity of 125 cc and then modified it into a 6 stroke motorbike with twice the duration of combustion. The observed local atmospheric conditions at a relative humidity of about 76% rH, and the ambient temperature and pressure were around 24 ° C and 101.32kPa, respectively. The implementation of data retrieval with crankshaft rotation at intervals of 600 rpm from 2400 rpm to 7200 rpm.Using an anlyser gas, the MUB-2 six-stroke engine showed 12.36% CO levels, 27.30% HC levels, 30.8 CO2 levels % and 1.7% lower lambda than conventional four-stroke engines. This means that in the 6 stroke MUB-2 motor, the combustion process of the air and fuel mixture is more perfect than the conventional 4 stroke motor.